The effect of training background on oxidized lipoprotein lipids and antioxidant capacity in athletes and keep-fit runners - Välimäki, Iiro (fi=Turun yliopisto|en=University of Turku|, 2018)
Background: High-intensity acute exercise is known to induce oxidative stress and may lead to harmful oxidation of lipids, and protein and DNA damage. On the other hand, exercise is known to positively influence risk factors of atherosclerosis, such as LDL and HDL cholesterol. The role of oxidized LDL lipids as a major risk factor in atherosclerosis is well-established; however, the significance of oxidized HDL lipids has not yet been determined. Aim: The aim of this study is to investigate the acute and training effects of various types of physical exercise and training background on oxidation of LDL and HDL lipids and antioxidant capacity. The subject of this study consists of three different sets of data. A total of 223 individuals participated in the study, 188 of which were endurance runners, and 35 were ice hockey players. Participants ranged in age from 20–69 years old. Results: Regular low-intensity training and better maximal oxygen uptake leads to decreased oxidative stress levels compared with high-intensity training. Lactobacillus GG (LGG) probiotics do not protect endurance runners from oxidation of LDL lipids. Low levels of exercise combined with increased carbohydrate intake induces oxidation of LDL lipids within as little as 6-days. Acute physical exercise increases the concentration of oxHDLlipids in serum. Oxidative stress and the removal of lipid oxidation products by HDL are greater during athletes’ acute physical activity, and less during normal training. Conclusions: Low-intensity aerobic exercise training protects our bodies by decreasing the levels of oxidative stress compared with anaerobic and high-intensity exercises. Aerobic exercise especially decreases oxLDLlipids levels in the human body and, at the same time, increases the removal of lipid peroxides through transport mechanisms of HDL. The results presented in this thesis strengthen the role of aerobic exercise in preventing atherosclerosis and give a new aspect to the clearing protective role of HDL.

Harjoitustaustan vaikutus hapettuneisiin lipoproteiniinien lipideihin ja antioksidanttikapasiteettiin urheilijoilla ja kuntojuoksijoilla Tausta: Intensiteetiltään voimakkaan liikunnan tiedetään aiheuttava oksidatiivista stressiä aiheuttaen kudoksiin haitallista rasvojen, proteiinien ja DNA:n hapettumista. Toisaalta on todistettu liikunnan vaikuttavan positiivisesti valtimonkovettumataudin riskitekijöihin, kuten LDL –ja HDL-kolesteroliin. Hapettuneen LDL-kolesterolin rooli yhtenä merkittävämpänä riskitekijänä valtimonkovettumataudissa tiedetään, mutta hapettuneen HDL-kolesterolin merkitys on vielä epäselvä. Tavoitteet: Väitöskirjatyön tavoitteena on ollut tutkia fyysisen harjoittelun ja aerobisen kunnon vaikutusta pitkäaikaisessa ja akuutissa rasituksessa LDL ja HDL-lipidien hapettumiseen ja antioksidanttikapasiteettiin. Tutkimuksen koehenkilöt muodostuivat kolmen eri aineiston pohjalta. Tutkimukseen osallistui yhteensä 223 mieshenkilöä, joista kestävyysjuoksijoita oli 188 ja jääkiekkoilijoita 35. Ikähaitari tutkituilla oli 20-69 vuotta. Tulokset: Pitkäaikainen matala intensiteettinen harjoittelu ja parempi kestävyyskunto aiheuttavat vähemmän lipidien hapettumista kuin voimakas intensiteettinen harjoittelu. Lactobacillus GG (LGG) probiootit eivät suojaa kestävyysjuoksijoita LDL-lipidien hapettumiselta. Vähäinen aerobinen liikunta yhdistettynä hiilihydraattipitoiseen ruokavalioon lisää oxLDL -pitoisuutta merkittävästi jo lyhyessä ajassa. Akuutti fyysinen liikuntasuoritus nostaa oxHDL -pitoisuuksia verenkierrossa. OxHDL –pitoisuus nousee aikaisemmin, jos harjoitus vastaa urheilijan harjoitushistoriaa. Johtopäätökset: Aerobinen matala intensiteettinen liikunta suojaa elimistöä vähentämällä oksidatiivisen stressin pitoisuuksia anaerobiseen korkean intensiteetin liikuntaan verrattuna. Erityisesti aerobinen liikunta vähentää oxLDL –pitoisuuksia elimistössä ja samalla lisää hapettuneiden lipidien poiskuljetusta lisäämällä oxHDL –pitoisuuksia verenkierrossa. Tässä väitöskirjassa esitetyt tulokset vahvistavat aerobisen liikunnan roolia valtimonkovettumataudin ennaltaehkäisyssä ja toisaalta tuovat uuden näkökulman HDL:n suojaavasta roolista hapettuneiden lipidien poiskuljettajana.